Setting the agenda for clinical pharmacy in Qatar: thematic and content analyses of news media headlines - Diab M; Wilby KJ (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Background: Public awareness of the role of pharmacists and availability of pharmacy services in Qatar is low. As per agenda-setting theory, mass media may be contributing toward this problem by selecting and disseminating headlines and stories according their own objectives and not those of the profession. Objectives: The objective of this study was to examine the agenda set by mass media organizations in Qatar pertaining to the profession of pharmacy and to determine the frequency of professional identifiers that appear within news headlines. Methods: Publicly available news headlines published between November 2016 and November 2018 were obtained from local news websites. Thematic analysis was performed using agenda-setting theory to explore how the public's agenda was set for pharmacy practice in Qatar. Content analysis was used to determine the proportion of headlines that contained a professional identifier linking the news report to the pharmacy profession. Results: A total of 81 headlines were included in the analysis. The agenda for pharmacy practice in Qatar was set according to two themes: achievement and outreach/engagement. Achievement related to awards, use of new technologies, interprofessional education, and novel student training accomplishments. Outreach/engagement reported student and pharmacist involvement upon completion of a health awareness event. Approximately half (47%) of headlines contained a professional identifying word linking the headline to the profession of pharmacy. Conclusions: The findings of this study demonstrate that the mass media's agenda for the pharmacy profession in Qatar does not inform the public of pharmacist's services or expanded scopes of practice. Furthermore, a lack of professional identifiers within headlines likely limits the public's agenda of pharmacist roles. The pharmacy profession must work collaboratively with news media to better align the public's agenda with pharmacists' roles and services.